Numerical Investigation on Deep-Foundation Pit Excavation Supported by Box-Type Retaining Walls - Peng Peng; Weiyao Kong; Saishuai Huang; Yi Long; Yang Lu (Buildings)
In soft soil foundations, the utilization of box-type retaining walls as a support method represents a novel approach. This study focuses on investigating the key factors influencing lateral wall deflection and ground settlement behind the wall in deep excavation projects supported by box-type retaining walls. Based on a practical engineering case in Shanghai, the large deformation Lagrangian numerical simulation software FLAC-3D is employed to simulate the displacement of box-type retaining walls as well as the surface settlement surrounding the excavation pit during the excavation process of deep-foundation pits. This research encompasses aspects such as the box size, the filling material within the box, and the constituent materials of the retaining wall. Ultimately, it is concluded that variations in the size of the box-retaining wall have a significant impact on wall deflection and surrounding ground settlement, while the filling material and constituent materials have relatively minor effects. This study provides a theoretical basis and scientific reference for the design and construction of box-type retaining walls in deep-foundation pit engineering.